Electric-field effect on photoluminescence of lead-halide perovskites. (September 2019) - Yi, Hee Taek; Rangan, Sylvie; Tang, Boxin; Frisbie, C. Daniel; Bartynski, Robert A.; Gartstein, Yuri N.; Podzorov, Vitaly
Graphical abstract: Abstract: With the development of novel semiconductors for optoelectronic applications, new device functionalities utilizing unique characteristics of emerging materials can be particularly appealing. Here, we demonstrate a reversible control of photoluminescence (PL) emission from lead-halide perovskites achieved in perovskite electric-double-layer transistors. PL in several prototypical lead-halide perovskite compounds is shown to be reversibly tuned by a small gate voltage in the range ±1.2 V applied to the ionic-liquid gel on the perovskite surface, with the intensity modulation that can reach one to two orders of magnitude. This effect may be mediated by a reversible migration of oxygen ions affecting the crystal region near the interface with the ion gel. The resulting passivation (or activation) of non-radiative recombination centers (traps) by oxygen ions would then modulate the population of mobile photogenerated electrons and holes that give rise to PL, which is thus tuned with an electric "knob" (the gate) in these devices.